Seasonal prediction of rainfall variability for the West African Sudan-Sahel - Rauch, Manuel; Bliefernicht, Jan; Sawadogo, Windmanagda; Sy, Souleymane; Waongo, Moussa; Kunstmann, Harald (Frontiers in Water, 2025)
The Sudan-Sahel region in West Africa is highly vulnerable to rainfall variability, which poses significant challenges to agriculture and water resource management. This study provides an assessment of seasonal rainfall prediction models in the region, focusing on the West African Regional Climate Outlook Forum (WARCOF, 1998–2023), the latest generation of the seasonal forecasting system from the European Centre for Medium-Range Weather Forecasts (ECMWF SEAS5, 1981-2023), and a novel atmospheric circulation-pattern-based logistic regression model (1981–2023). The circulation-pattern-based model, which integrates key atmospheric dynamics like near-surface wind anomalies, outperforms both WARCOF and SEAS5 in predicting interannual rainfall variability. While WARCOF and SEAS5 demonstrate some predictive skill, both models exhibit biases: WARCOF has a dry bias, and SEAS5 displays both dry and wet biases. The circulation-pattern-based model, despite a slight wet bias, delivers more accurate categorical predictions and offers greater reliability. An economic value analysis reveals that the circulation-pattern-based model provides a broader range of positive economic outcomes, making it more suitable for decision-making across various cost-loss scenarios. By introducing this novel model and evaluating traditional forecasting techniques, this study lays the groundwork for more accurate and reliable seasonal rainfall predictions.